Leukaemia and non-Hodgkin's lymphoma: incidence in children and young adults resident in the Dounreay area of Caithness, Scotland in 1968-91. Issue 3 (June 1994) - Black, R J; Sharp, L; Harkness, E F; McKinney, P A
Abstract : STUDY OBJECTIVE–To review the incidence of leukaemia and non-Hodgkin's lymphoma in children and young adults in the area less than 25 km from the Dounreay nuclear installation and the remainder of the Kirkwall postcode area in the full time period for which data are now available (1968-91), and to determine whether the excess incidence reported in the period up to 1984 has continued in subsequent years. DESIGN–Geographical incidence study. SETTING–The Kirkwall postcode area of Scotland. SUBJECTS–Children and young adults resident in the area in the period 1968-91. MAIN RESULTS–Observed numbers of cases of leukaemia and non-Hodgkin's lymphoma and observed to expected ratios with expected numbers based on Scottish national rates were determined. In 1968-91, 12 cases were observed compared with 5.2 expected in the zone < 25 km from the Dounreay plant (p = 0.007). In the latest period, 1985-91, which has not previously been examined, four cases were observed compared with 1.4 expected (p = 0.059). CONCLUSION–The observation of an excess of borderline statistical significance in 1985-91 following the substantial excess incidence which occurred in the early 1980s suggests that the incidence of leukaemia and non-Hodgkin's lymphoma in this area should continue to be a matter of concern. The phenomenon of high incidences of childhood and young adult leukaemia and lymphoma near some nuclear installations in isolated areas is yet to be explained, but certain aspects of the data examined in the present report are consistent with the hypothesis of an infectious aetiology for leukaemia in very young children.